INTEGRASI APLIKASI WEB DAN SMS GATEWAY PADA TPI GEMPOLSARI MENGGUNAKAN PHP DAN MySQL - Adiyanto, Adiyanto; Suraya, Suraya; Sutanta, Edhy (Jurnal Jarkom, 2013)
ABSTRACT Fish Auction ( TPI ) Gempolsewu Village in Kendal as a place to conduct the auction of fish the fishermen who sell fish to consumers by intermediaries TPI . TPI is managed by KUD